Is there a non-linear relationship of market value with cash and ownership? - Stavros E. Arvanitis; Theodoros V. Stamatopoulos; Dimitris Terzakis (SPOUDAI - Journal of Economics and Business, 2018)
The paper provides new evidence on the way that both the cash and ownership influence firms' market value in the Athens Stock Exchange (ASE) within the Eurozone (2000-2015). Based on corporate governance theory and critical analysis we use the dynamic panel data econometrics, in order to get consistent estimations of the impact of firms' cash and ownership upon either the return on equity or the Tobin's Q ratio. It is confirmed the dominance of the ownership pattern on these determinants of firms' value. Actually, we have found an inverse-U-shape value-ownership relationship, while practically, there's no-effect of cash on business efficiency. Unlike the previous studies, the findings support not only the interest alignment hypothesis, or the ownership could be a substitute for weak legal and institutional environment, but also the expropriation of outright majority ownership (large shareholder) against the minority one. In addition, the constantly changing optimal level of cash due to the unstable economic environment is a possible explanation of the insignificant cash variable. The estimated 40% of the equity as optimal level of ownership concentration maximizing market value of firms in the ASE could be useful for candidate investors.
Keywords: C58; G32; G34; 330; Corporate governance; Cash management; Corporate ownership concentration; Agency theory; Eurozone crisis; Tradeoff theory